Pylephlebitis Caused by Fusobacterium nucleatum in a Septuagenarian Healthy Caucasian Male: Atypical Presentation of Lemierre’s Syndrome - Muhammad Abbas; Monica Ioana Constantin; Akshay Narendra (Case Reports in Infectious Diseases)
Lemierre’s syndrome (LS) is characterized by thrombophlebitis of the internal jugular vein caused primarily by Fusobacterium necrophorum. LS is usually suspected in fit young adults with prolonged or prior pharyngeal infection. Atypical Lemierre’s syndrome is commonly defined as Fusobacterium-associated thrombophlebitis outside the head-neck veins and usually occurs in older patients than typical Lemierre’s syndrome. Here we present a case of atypical LS in a septuagenarian healthy Caucasian male with no prior history of pharyngitis and in whom both computed tomography (CT) and magnetic resonance imaging (MRI) demonstrated partial portal vein thrombosis associated with Fusobacterium nucleatum. This case report confirms previous reports of Fusobacterium nucleatum-associated LS variants presenting with abdominal vein thrombosis and illustrates clinical recovery after a combination of anticoagulation and antibiotic therapy.